Bilirubin: an autofluorescence bile biomarker for liver functionality monitoring. Issue 10 (25th April 2013) - Croce, Anna C.; Ferrigno, Andrea; Santin, Giada; Vairetti, Mariapia; Bottiroli, Giovanni
Abstract Excitation at 366–465 nm of bilirubin in aqueous solution with solubilizing agents results in emission spectra composed by two main bands. The variation of their relative contributions as shown by changes in the spectral shape are consistent with the bilirubin bichromophore nature. This latter accounts for an exciton‐coupling phenomenon, intramolecular interchromophore energy transfer efficiency being affected by microenvironment. Excitation at 366 nm, despite the poor absorption of bilirubin, gives rise to appreciable emission signals from both pure compounds and bile – collected from functionally altered rat livers – favouring the spectral shape response to environment and molecular conformation changes. As compared to the merely bile flow estimation, real‐time detection of fluorescence, revealing composition variations, improves near‐UV optical‐biopsy diagnostic potential in hepatology. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)